2000
DOI: 10.1097/00001756-200004270-00041
|View full text |Cite
|
Sign up to set email alerts
|

BN 80933 Inhibits F2-isoprostane elevation in focal cerebral ischaemia and hypoxic neuronal cultures

Abstract: Formation of the lipid peroxidation product 8-epi-prostaglandin2alpha (8-epi-PGF2alpha) a bioactive marker of oxidative stress, was quantified in in vitro and in vivo models of neuronal death. In culture media of primary rat cortical neurones exposed to hypoxia followed by reoxygenation, a 3.7-fold increase of 8-epi-PGF2alpha concentration was observed in comparison to control cells. In rats submitted to 2h middle cerebral artery occlusion followed by a 22h reperfusion period, a 27-fold increase of 8-epi-PGF2a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 5 publications
1
19
1
Order By: Relevance
“…Upon ischemia, free PGE 2 and PGD 2 were signifi cantly increased with a more profound increase in PGD 2 mass ( Table 2 ), which is consistent with previous studies ( 29,37,38,46 ). Total (free plus esterifi ed) isoPGs were significantly increased ‫ف‬ 2-fold, which is consistent with increased oxidative stress upon ischemia ( 47,48 ) and consistent with the increase in free isoPGE 2 /D 2 levels in decapitated rat brains ( 38 ). The found values for brain isoPG are in the range of the previously reported values for rat liver ( 15 ).…”
Section: Brain Tissue Isopg Separation and Quantifi Cation Under Basasupporting
confidence: 88%
“…Upon ischemia, free PGE 2 and PGD 2 were signifi cantly increased with a more profound increase in PGD 2 mass ( Table 2 ), which is consistent with previous studies ( 29,37,38,46 ). Total (free plus esterifi ed) isoPGs were significantly increased ‫ف‬ 2-fold, which is consistent with increased oxidative stress upon ischemia ( 47,48 ) and consistent with the increase in free isoPGE 2 /D 2 levels in decapitated rat brains ( 38 ). The found values for brain isoPG are in the range of the previously reported values for rat liver ( 15 ).…”
Section: Brain Tissue Isopg Separation and Quantifi Cation Under Basasupporting
confidence: 88%
“…However, the equivalent values for all the control levels implies that the increases specific to ipsilateral brain tissue is the true increase due to ischemia and reduction by tamoxifen to the control levels means that tamoxifen completely inhibits the ischemia-induced increases. Marin et al (2000) reported relatively much lower levels in contralateral brain tissue from rMCAo animals. In these studies the removed hemispheres were frozen in liquid N 2 and the isoprostane levels of the entire hemispheres measured with no dissection of the different regions.…”
Section: Antioxidant Activity and Tamoxifen-induced Neuroprotectionmentioning
confidence: 92%
“…To see whether this protection correlated with antioxidant activity under the same conditions we tested the antioxidant effects of 5 mg/kg tamoxifen given 3 hours after initiation of ischemia as measured by effects on isoprostane appearance. We chose to study effects on isoprostane levels as these compounds are emerging as stable markers of lipid peroxidation and hence free radical damage in cerebral ischemia (Marin et al, 2000), For IsoPs in the striatum, there was a significant effect of treatment (p = 0.015) and a significant interaction effect (p = 0.025), reflecting a difference in the response of ischemic versus nonischemic tissue to the effect of tamoxifen. The IsoPs levels in the ischemic vehicle-treated striatum were significantly higher than all other striatal tissue (all p values < 0.038).…”
Section: Antioxidant Activity Of Tamoxifenmentioning
confidence: 99%
See 2 more Smart Citations